Smartphone addiction among nursing students in higher learning institutions / Siti Khuzaimah Ahmad Sharoni, Zarifah Abu Bakar and Najihan Abu Bakar - Ahmad Sharoni, Siti Khuzaimah; Abu Bakar, Zarifah; Abu Bakar, Najihan (Universiti Teknologi Mara Cawangan Pulau Pinang, 2020)
Smartphone has more advanced computing skill hence making the use of a smartphone possible for varied purposes and objectives. However, the negative side of the smartphone usage is ignored by many people especially among the younger generation. Thus, this study is to provide some information about smartphone addiction among nursing students in a public university. Cross-sectional survey was carried out at Universiti Teknologi MARA (UiTM) Puncak Alam Campus, from December 2018 to January 2019. The questionnaire was distributed to the nursing students to assess their smartphone addiction. A total of 212 questionnaires were distributed during the data collection procedure and out of these 200 questionnaires were completed and returned by the respondents. The total mean of smartphone addiction scale was found to be moderate. The study found that there is a correlation between smartphone addiction with age and Cumulative Grade Point Average. The study concludes that it is important to create awareness on smartphone addiction especially among younger students and students those who have low CGPA scores. Several recommendations were put forward as guidelines to minimize smartphone addiction.